Targeted delivery of a vaccine protein to Langerhans cells in the human skin via the C‐type lectin receptor Langerin. Issue 11 (9th January 2022) - Bellmann, Lydia; Strandt, Helen; Zelle‐Rieser, Claudia; Ortner, Daniela; Tripp, Christoph H.; Schmid, Sandra; Rühl, Julia; Cappellano, Giuseppe; Schaffenrath, Sandra; Prokopi, Anastasia; Spoeck, Sarah; Seretis, Athanasios; et al.
Abstract: Human skin is a preferred vaccination site as it harbors multiple dendritic cell (DC) subsets, which display distinct C‐type lectin receptors (CLR) that recognize pathogens. Antigens can be delivered to CLR by antibodies or ligands to boost antigen‐specific immune responses. This concept has been established in mouse models but detailed insights into the functional consequences of antigen delivery to human skin DC in situ are sparse. In this study, we cloned and produced an anti‐human Langerin antibody conjugated to the EBV nuclear antigen 1 (EBNA1). We confirmed specific binding of anti‐Langerin‐EBNA1 to Langerhans cells (LC). This novel LC‐based vaccine was then compared to an existing anti‐DEC‐205‐EBNA1 fusion protein by loading LC in epidermal cell suspensions before coculturing them with autologous T cells. After restimulation with EBNA1‐peptides, we detected elevated levels of IFN‐γ‐ and TNF‐α‐positive CD4 + T cells with both vaccines. When we injected the fusion proteins intradermally into human skin explants, emigrated skin DC targeted via DEC‐205‐induced cytokine production by T cells, whereas the Langerin‐based vaccine failed to do so. In summary, we demonstrate that antibody‐targeting approaches via the skin are promising vaccination strategies, however, further optimizations of vaccines are required to induce potent immune responses. Abstract : Antigen delivery to skin dendritic cells can be achieved by targeting either Langerin or DEC‐205 expressed on Langerhans cells and dermal dendritic cells. This study demonstrates that Langerin delivers proteins to Langerhans cells in vitro, however, DEC‐205 was more potent as vaccination approach when tested in a skin explant model.